Blood Count on a Smartphone Microscope: Challenges - Moravapalle, Uma P.; Deshpande, Amit; Kapoor, Ashish; Ramjee, Ramachandran; Ravi, Priya (HotMobile, 2017)
Low-cost lenses with magnifications of 150-200x are being sold in the market today as accessories for mobile smartphones. Attaching these lenses to a smartphone camera creates low-cost, ultra-portable digital microscopes, with a potential for significant impact on applications in a variety of fields such as healthcare, agriculture, education etc. In this paper, we consider a low-cost do-it-yourself Complete Blood Count (CBC) application using a smartphone microscope. We discuss several unique challenges that come up in implementing this application that include preparing the blood sample, correcting the small field of view and blur of the lens, and automating the cell counting procedure. We present our approach to overcome these challenges and report early promising results on counting red blood cells.